ASSOSIATION OF SERUM MAGNESIUM LEVELS WITH HOMEOSTATIC MODEL ASSESSMENT OF INSULIN RESISTANCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS ON METFORMIN OR PIOGLITAZONE - HUWAINAN NISA NASUTION; SONY WIBISONO MUDJANARKO; DWI APRILAWATI; AGUNG PRANOTO (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Background: Magnesium is known to be associated with insulin resistance in type 2 diabetes mellitus (DM) resulting in the accelerated progression of the disease causing the risk of complications in type 2 DM. In a hypomagnesemic state, there is a decrease in the phosphorylation of insulin receptor which leads to an increase in insulin resistance. Methods: The inclusion criteria were the patients of type 2 DM who had already used metformin or pioglitazone with a body mass index of <30 kg/m2. An examination of magnesium nutrient intake on the patients was carried out with a validated food frequency questionnaire of nutrient intake for the past 3 days by a nutritionist. Fasting plasma glucose was analyzed using Roche/Hitachi Cobas C System. Fasting insulin was analyzed using the Elecsys and Cobas E Immunoassay Analyzers. Serum magnesium level was analyzed using Roche/Hitachi Cobas C 311/501 System. Results: The study involved 41 subjects of patients with type 2 DM. The mean of magnesium nutrient intake was still low with an average of 207.2 ± 52.9 mg/day. The mean value of serum magnesium levels was 2.04 ± 0.19 mg/dl. The mean of homeostatic model assessment of insulin resistance (HOMA-IR) was 4.82 ± 5.66. The lower level of the serum magnesium had a significant correlation with HOMA IR. Conclusion: The nutrient intake containing magnesium is lower than recommendation. There is a significant negative correlation between the magnesium level and HOMA-IR on type 2 DM on metformin or pioglitazone.